Accent and Ugandan Students’ Comprehension of Mathematical Concepts and Terms: An Experimental Study. - Kemeza, Imelda; Balimuttajjo, Sudi; Sarvate, Dinesh G. (African Journal of Teacher Education, 2020)
The embrace of diversity and multiculturalism in education facilitates the broadening of students’ Experiences as they engage with teachers and classmates from backgrounds different than their own. However, while the positive effects of diversity on students are apparent, few studies have examined possible negative challenges that diversity might have on students. Where most subject matter is taught via classroom lectures and the lecture material is presented by a speaker with a different accent than the student is used to hearing, does it make the material harder for the student to understand? On the other hand, could it increase the focus and engagement required by the students in the classroom, and in the process increase their understanding? In this vein, our research sought understand whether students’ learning of the subject matter hindered when they are taught material by a teacher with a different accent. To this end, we designed a simple experiment with a small group of undergraduate students in Uganda, to address this question, the result of which we present in this study.
Keywords: accent; English speaker; comprehension; mathematical concepts; Uganda